DEVELOPMENT OF GOOGLE SITES LEARNING MEDIA TO INCREASE STUDENT LEARNING INTEREST IN GEOGRAPHY SUBJECTS AT SMAN 10 FAJAR HARAPAN BANDA ACEH - Safinatun Najah; Ernawati Ernawati (GeoEco, 2025)
This study aims to determine the feasibility of Google Sites learning media and the effect of using Google Sites learning media in increasing student interest in learning. The method used in research is the ADDIE model, which involves development research and experimental methods. Based on the study's results on learning media development, the Google site, expert validation results obtained from material experts by 95% criteria, are very suitable, and media experts by 76%. The results of data analysis from student questionnaires regarding student interest in learning geography in experimental and control classes obtained results in hypothesis testing show that the value of t count > t table, namely t count = 3.168, is greater than t table 1.999, then H0 is rejected. The calculated significance level is 0.002, which is smaller than 0.05 (Sig (2-tailed <0.05). This means that H0 is rejected, and Ha is accepted. It is concluded that there is a difference in student interest in learning geography between the control and experimental classes. Furthermore, from the results of the average interest value of the experimental class of 80.906 and the control class of 76.468, it is known that the average of the experimental class is higher than the average of the control class. It can be concluded that there is a significant effect of using Google Sites learning media to increase learning interest in learning geography of class X students at SMAN 10 Fajar Harapan.